THE INFLUENCE OF INFLATION, ECONOMIC GROWTH, EXCHANGE RATES, AND DIVIDEND POLICY ON STOCK PRICES (A Case Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange During the 2019–2023 Period) - Zuliko, Atmah; Hatta Setiabudhi; Mutia Pamikatsih (LPPM Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
This study aims to analyze the influence of macroeconomic variables such as inflation, economic growth, and exchange rates, along with corporate policy factors like dividend policy, on stock prices in the property and real estate sector in Indonesia. The research is motivated by the high sensitivity of this sector to external economic changes and internal financial decisions, especially during the volatile economic period of 2019–2023, which includes the impact of the COVID-19 pandemic and subsequent recovery efforts. The property and real estate sector plays a vital role in national economic development due to its strong linkages with labor absorption and multiple supporting industries. The study employs a quantitative research method with a panel data regression approach to examine 1companies listed1 on the Indonesia Stocki Exchange (IDX). The sample was selected using purposive sampling based on data completeness criteria, covering a five-year period. Secondary data were sourced from IDX, the Central Bureau of Statistics (BPS), and Bank Indonesia. Several statistical tests were carried out including classical assumption tests, model selection tests (Chow, Hausman, and LM), as well as hypothesis testing using t-test and F-test, followed by coefficient of determination analysis. The Random Effect Model (REM) was identified as they most appropriate estimation method for this study. The results reveal that inflation and dividend policy have a significant positive effect on stock prices, suggesting that moderate inflation and consistent dividend payouts are perceived positively by investors. In contrast, economic growth and exchange rates show a significant negative influence, indicating that the sector has not fully benefited from post-pandemic recovery and remains vulnerable to currency fluctuations. These findings highlight the importance of both macroeconomic stability and sound financial management practices in influencing investor confidence and stock performance in the property sector. The study offers practical implications for investors, financial managers, and policymakers in designing strategies to enhance investment value and mitigate risks in the capital market.